Attraction of the Origin, or Reflections on how to Change the Text Without Cheat on the Author (on the Example of Severyanin’s Nocturne) - Беднарчик, Анна (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The article discusses two translations of Igor Severyanin’s poem Nocturne made by the author of this paper. The first one is a translation that interferes with the structure of the original, while the second one preserves the formal structure of the original text. The analysis of Polish variants of the poem has shown that regardless of the formal change made, the translation can preserve the semantics, style and character of the original, which also allows the reader to convey its artistic value to the translation. On the other hand, the preservation of the original form of the poem may lead to the loss of the artistic character of the original.